The cruelest month eaudiobook - Penny, Louise (Chief Inspector Armand Gamache, 2015)
Listen to the series that inspired Three Pines on Prime Video. "Narrator Ralph Cosham evokes the idyllic Quebec village of Three Pines with skillful handling of the often funny, often conflicted people who live there." — AudioFile Magazine The Cruelest Month is the third installment in Louise Penny's award winning Three Pines mystery series featuring the wise and beleaguered Inspector Armand Gamache. "Many mystery buffs have credited Louise Penny with the revival of the type of traditional murder mystery made famous by Agatha Christie ... " —Sarah Weinman Welcome to Three Pines, where the cruelest month is about to deliver on its threat. It's spring in the tiny, forgotten village; buds are on the trees and the first flowers are struggling through the newly thawed earth. But not everything is meant to return to life. . . When some villagers decide to celebrate Easter with a séance at the Old Hadley House, they are hoping to rid the town of its evil—until one of their party dies of fright. Was this a natural death, or was the victim somehow helped along? Brilliant, compassionate Chief Inspector Armand Gamache of the Sûreté du Québec is called to investigate, in a case that will force him to face his own ghosts as well as those of a seemingly idyllic town where relationships are far more dangerous than they seem. A Macmillan Audio production from St. Martin's Press